2010
DOI: 10.1261/rna.2186510
|View full text |Cite
|
Sign up to set email alerts
|

Retention of spliceosomal components along ligated exons ensures efficient removal of multiple introns

Abstract: The majority of mammalian pre-mRNAs contains multiple introns that are excised prior to export and translation. After intron excision, ligated exon intermediates participate in subsequent intron excisions. However, exon ligation generates an exon of increased size, a feature of pre-mRNA splicing that can interfere with downstream splicing events. These considerations raise the question of whether unique mechanisms exist that permit efficient removal of introns neighboring ligated exons. Kinetic analyses of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 50 publications
4
19
0
Order By: Relevance
“…First, we downregulated EJC associated splicing factors such as Acinus and SRSF1, but none of the EJC-dependent splicing events depended on these factors. Second, Crabb and colleagues have shown that EJC deposition did not affect subsequent splicing kinetics in a reporter with two introns [58]. We also found that minigene vectors from EJC-regulated splicing events showed no difference in splicing with or without a predeposition of EJC (data not shown).…”
Section: Discussionsupporting
confidence: 52%
“…First, we downregulated EJC associated splicing factors such as Acinus and SRSF1, but none of the EJC-dependent splicing events depended on these factors. Second, Crabb and colleagues have shown that EJC deposition did not affect subsequent splicing kinetics in a reporter with two introns [58]. We also found that minigene vectors from EJC-regulated splicing events showed no difference in splicing with or without a predeposition of EJC (data not shown).…”
Section: Discussionsupporting
confidence: 52%
“…Thus, our data support the notion that CBC helps recruit U1 snRNP to the first 5 ′ ss (Lewis et al 1996b), not by direct interactions with U1 but instead indirectly through the U4/U6·U5 snRNP. Moreover, the U1 snRNP is retained on multiple intron-containing pre-mRNAs after the first splicing event, rendering subsequent splicing more efficient (Crabb et al 2010). Indeed, splicing of both FOS introns 1 and 3 was CBC dependent, suggesting-together with the observed snRNP profiles-that CBC may help retain the U1 snRNP on nascent RNA until all introns are removed.…”
Section: Cbc Depletion Impairs Cotranscriptional Spliceosome Assemblymentioning
confidence: 97%
“…In various splicing reporters, normal 4.1 pre-mRNAs, and aberrant patient transcripts, the nested intrasplicing step consistently occurred at a composite 3= splice site generated by juxtaposition of the iE branch point with the next AG dinucleotide downstream of the first-step acceptor. We speculate that the second acceptor is selected by a scanning mechanism that would not require de novo exon definition of the ligated sequences in the first step (8). In contrast, each successive step of recursive splicing involves a new composite 5= splice donor site formed when an exon is spliced to a downstream "zero-length exon" containing adjacent 3= and 5= splice sites.…”
Section: Discussionmentioning
confidence: 99%